(untitled) (Health Renaissance, 2015)
Background: The TORCH complex is a medical acronym for a set of bacterial, protozoal and viral infections (Toxoplasma, Rubella, Cytomegalovirus and Herpes simplex). Perinatal infection with TORCH can result in foetal complications depending upon the period of gestation, duration of infection, severity of infection and immune status of foetus. Objective: To determine the association of TORCH IgG and IgM antibodies in women with spontaneous abortion. Methods: It was a prospective observational study conducted in the Department of Obstetrics and Gynaecology of Tribhuvan University Teaching Hospital, IOM, Maharajgunj, Kathmandu, Nepal. The study duration was for one year - Baisakh 2067 to Chaitra 2067 (April 2010–March 2011). During the study period, 153 women with spontaneous abortion, fulfilling the inclusion criteria were taken for TORCH IgM and IgG serological study. Results: In the present study, highest occurrence of IgM only antibody was of Toxoplasma occurring in 16.3% of enrolled women. Both IgM and IgG were negative for Toxoplasma in 39.9% of enrolled women indicating risk for Toxoplama infection. IgG positivity to Cytomegalovirus was found in 124 (81%) women. Both IgM and IgG positivity for Rubella was found in 35.3% of enrolled women. Conclusion: In the present study on analysing the association of TORCH antibodies in women with spontaneous abortion, recent infection of Toxoplasma was most commonly associated. However a larger study should be carried out to confirm the finding of the present study. Health Renaissance 2014;12(2): pp: 124-129